Asian’s conservative attitudes toward sex and its impacts on women’s sexual practices and reproductive health - Roomruangwong, Chutima; Neill Epperson, C. (Chulalongkorn Medical Journal, 2023)
Asians, in general, are more conservative about sexual and reproduction-related issues than individuals from Western countries. These conservative attitudes often lead to reticence to communicate about sexual and reproductive issues, hindering attempts to promote sex education or contraceptive knowledge, which can heighten the risk for sexually transmitted disease, unintended pregnancy, induced abortion, and emotional problems. It is critical for health care providers working with Asian women to understand them within this cultural context in order to provide gynecologic and reproductive care with sensitivity and compassion. Although this issue has been mentioned in some studies conducted in Asia or with Asian immigrants, none have examined this attitude across Asian countries and how it may impact Asian women’s physical and behavioral health. The authors seek to fill up this gap by reviewing the potential origins and consequences of conservative sexual attitudes among Asian populations in order to highlight areas of potential intervention to improve sexual and reproductive health of women in Asian cultures.